2001
DOI: 10.1021/ed078p256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Success of Hispanic-Surname Students in First-Semester General Chemistry

Abstract: This study was undertaken to identify methods and variables that affect classroom instruction, student achievement, and retention in a first-semester general chemistry course at a designated minority (primarily Hispanic) public institution of higher education. The course was a large-group lecture class (n = 241) of first-semester general chemistry that included 92 students with Hispanic surnames. Background information was gathered on the students' university-required entrance examinations, results from a logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…His analyses showed a strong correlation between SAT math score and general chemistry grades, with no significant differences in any of the subsets except for chemistry/biochemistry majors whose grades were underpredicted. More recently, Mason and Mittag (2001) reported on a study of Hispanic‐surnamed students in first‐semester general chemistry, and gave evidence that mathematical experience, measured by the highest level of mathematics completed, was the strongest predictor of success for all students in the class.…”
Section: Related Studiesmentioning
confidence: 99%
“…His analyses showed a strong correlation between SAT math score and general chemistry grades, with no significant differences in any of the subsets except for chemistry/biochemistry majors whose grades were underpredicted. More recently, Mason and Mittag (2001) reported on a study of Hispanic‐surnamed students in first‐semester general chemistry, and gave evidence that mathematical experience, measured by the highest level of mathematics completed, was the strongest predictor of success for all students in the class.…”
Section: Related Studiesmentioning
confidence: 99%
“…The unexpected higher correlation when calculators were not used led the NSA team to further investigations. As is well-documented, Chem 1 to Chem 2 courses report historically high DFW rates (students who make grades of D or F or withdraw from a course) (Martin, 1942;Hovey & Krohn, 1958;Rowe, 1983;McFate & Olmsted, 1999;Legg, Greenbowe, & Legg, 2001;Mason & Mittag, 2001;Wagner, Sasser & DiBiase, 2002;Reardon et al, 2010;Ford, Broadway, & Mason, 2023). The diagnostic used in this study goes beyond arithmetic skills.…”
Section: Instrumentmentioning
confidence: 97%
“…After understanding the baseline for all students, we then looked at our groups of interest. There were three comparisons that we chose to explore based on our concerns with potential inequities and the availability of enough data to make a meaningful comparison: (1) transfer students (Wesemann, 2005;Stitzel and Raje, 2021), (2) female students (Liu et al, 2017), and (3) Hispanic students (Mason and Mittag, 2001). As for the comparisons between time points, we focused the comparisons for these groups based on effect size instead of simple significance testing as simply commenting on significance can either lead us to focus on trivial differences that simply meet a threshold of statistical significance or ignore large differences that simply did not meet a threshold of statistical significance.…”
Section: Demographic Comparisons (Research Question 1)mentioning
confidence: 99%
“…For example, it has been reported that female students typically have lower motivation than their peers in general chemistry (Liu et al, 2017). Additionally, there are reports showing how motivation is correlated to early college academic success among Hispanic students (Kaufman et al, 2008) while other reports demonstrate Hispanic students pass general chemistry at a rate lower than their peers (Mason and Mittag, 2001). When considering how students interact with each other in a PLTL setting, it is valuable to know how these differences are either increased, maintained, or decreased as a result of social influence in order to better plan activities to promote student learning and motivation.…”
Section: Student Experiences Entering Chemistrymentioning
confidence: 99%